Rapid, cost-effective identification of group A streptococci and enterococci by pyrrolidonyl-beta-naphthylamide hydrolysis. - Wellstood, S A (1987)
Group A streptococci and enterococci were identified by two L-pyrrolidonyl-beta-naphthylamide (PYR) hydrolysis tests. One uses Minitek PYR disks (BBL Microbiology Systems, Cockeysville, Md.); the other uses a swab impregnated with PYR reagent. Both tests and Strep-A-Chek (EY Laboratories, San Mateo, Calif.), a commercially available PYR test, were compared with conventional methods. The PYR methods correctly identified all strains of group A streptococci and enterococci tested.